General ability and specific cognitive functions are lower in children with epilepsy after perinatal ischemic stroke - Vaher, Ulvi; Männamaa, Mairi; Laugesaar, Rael; Ilves, Norman; Ilves, Nigul; Loorits, Dagmar; Kool, Pille; Ilves, Pilvi (Frontiers in Stroke, 2024)
Introduction Epilepsy develops in one third of children after perinatal stroke. Both epilepsy and stroke may be risk factors for impaired cognitive abilities. How the development of epilepsy is related to the cognitive profile of children with perinatal stroke is still unclear. The aim of the study was to evaluate general and specific cognitive functions in children with epilepsy and children without epilepsy after perinatal ischemic stroke. Methods The study group consisted of 51 children with perinatal ischemic stroke confirmed by magnetic resonance imaging: 27 (53%) children with arterial ischemic stroke and 24 (47%) with periventricular venous infarction. Magnetic resonance imaging and electroencephalography were performed in all patients after the neonatal period. Epilepsy was diagnosed if the child had at least two unprovoked seizures occurring >24 h apart or one unprovoked seizure with a high recurrence risk. Cognitive assessments were performed using the Kaufman Assessment Battery for Children, Second Edition, at the age of ≥7 years. General ability (Fluid Crystallized Index, Mental Processing Index, Non-verbal Index) and specific cognitive functions (sequential processing, simultaneous processing, learning, planning, knowledge) were evaluated. Results At the median age of 19.3 years (interquartile range 14.0–22) at the time of follow-up for epilepsy, 14 (27.5%) patients had developed epilepsy, and 37 (72.5%) patients were without epilepsy. All general cognitive ability scores were lower in children with epilepsy compared to children without epilepsy. Among specific cognitive functions, simultaneous processing, planning, and knowledge were lower in children with epilepsy compared to children without epilepsy: simultaneous processing mean [78.5, 95% CI: [69.8, 87.2], vs. 96.9, 95% CI [90, 103.9], p = 0.0018]; planning mean [82.5, 95% CI: [73, 92], vs. 96.2, 95% CI: [88.7, 103.6], p = 0.026]; knowledge median (25th, 75th percentile): 80.5 (75, 87) vs. 92 (84, 108), p = 0.023. Conclusion Children with epilepsy after perinatal ischemic stroke have lower general cognitive abilities compared to children without epilepsy. The profile of the subscales indicates lower verbal abilities and executive functions in children with epilepsy. Children with post-stroke epilepsy need targeted cognitive monitoring for early aimed rehabilitation and for establishing an adapted learning environment.